Two Years of Evolutionary Dynamics of SARS-CoV-2 in Mexico, With Emphasis on the Variants of Concern - Flores-Alanis, Alejandro; Delgado, Gabriela; Espinosa-Camacho, Luis F.; Rodríguez-Gómez, Flor; Cruz-Rangel, Armando; Sandner-Miranda, Luisa; Cravioto, Alejandro; Morales-Espinosa, Rosario (Frontiers in Microbiology, 2022)
Background: The advance of the COVID-19 pandemic and spread of SARS-CoV-2 around the world has generated the emergence of new genomic variants. Those variants with possible clinical and therapeutic implications have been classified as variants of concern (VOCs) and variants of interest (VOIs). Objective: This study aims to describe the COVID-19 pandemic and build the evolutionary and demographic dynamics of SARS-CoV-2 populations in Mexico, with emphasis on VOCs. Methods: 30,645 complete genomes of SARS-CoV-2 from Mexico were obtained from GISAID databases up to January 25, 2022. A lineage assignment and phylogenetic analysis was completed and demographic history for Alpha, Gamma, Delta and Omicron VOCs, and the Mexican variant (B.1.1.519) was performed. Results: 148 variants were detected among the 30,645 genomes analyzed with the Delta variant being the most prevalent in the country, representing 49.7% of all genomes. Conclusions: The COVID-19 pandemic in Mexico was caused by several introductions of SARS-CoV-2, mainly from the United States of America and Europe, followed by local transmission. Regional molecular epidemiological surveillance must implement to detect emergence, introductions and spread of new variants with biologically important mutations.